Transdiagnostic assessment in neurodevelopment: a systematic review - Belduma Cabrera, Karla Yaritza (My University, 2025)
Neurodevelopmental disorders (NDDs), such as ASD, ADHD, and intellectual disability, have increased in global prevalence, highlighting the limitations of categorical diagnostic approaches (DSM-5, ICD-11), which fail to reflect clinical heterogeneity and comorbidity. In this context, transdiagnostic models such as RDoC and HiTOP emerge as dimensional alternatives that allow for the understanding of shared processes across disorders. Following PRISMA 2020 guidelines, a systematic review analyzed 125 studies published between 2015 and 2025 in Scopus, PubMed, and WOS. The results indicate that dimensions such as emotion regulation, executive functions, social cognition, and sleep better explain clinical complexity than traditional categories. The findings show the application of theoretical frameworks such as RDoC, HiTOP, and latent class analyses, identifying the limited sensitivity and clinical overlap of categorical models, along with empirical evidence on transversal processes such as emotion regulation, executive functions, and neurofunctional biomarkers, while recognizing the advantages of the transdiagnostic approach for more precise and contextualized interventions in clinical and educational settings. In conclusion, this approach provides a more inclusive and coherent framework consistent with the complexity of neurodevelopment
Los trastornos del neurodesarrollo (TND), como el TEA, el TDAH y la discapacidad intelectual, han incrementado su prevalencia global, poniendo en evidencia las limitaciones de los enfoques diagnósticos categoriales (DSM-5, CIE-11), que no logran reflejar la heterogeneidad ni la comorbilidad clínica. En este contexto, los modelos transdiagnósticos, como el RDoC y el HiTOP, emergen como alternativas dimensionales que permiten comprender procesos compartidos entre trastornos. Mediante una revisión sistemática siguiendo PRISMA 2020, se analizaron 125 estudios publicados entre 2015 y 2025 en Scopus, PubMed y WOS. Los resultados muestran que dimensiones como regulación emocional, funciones ejecutivas, cognición social y sueño explican mejor la complejidad clínica que las categorías tradicionales. Los resultados muestran la aplicación de marcos teóricos como RDoC, HiTOP y análisis de clases latentes, identificándose limitaciones del enfoque categorial por su baja sensibilidad y solapamiento clínico con evidencia empírica sobre procesos transversales como la regulación emocional, funciones ejecutivas y biomarcadores neurofuncionales, reconociendo las ventajas del transdiagnóstico para intervenciones más precisas y contextualizadas en los ámbitos clínico y educativo. En conclusión, este enfoque ofrece un marco más inclusivo y coherente con la complejidad del neurodesarrollo.
Keywords: TRASTORNOS DEL NEURODESARROLLO; EVALUACIÓN PSICOLÓGICA; DIMENSIONES CONDUCTUALES; MODELOS TRANSDIAGNÓSTICOS